Hubungan Tingkat Pengetahuan dan Sikap Ibu tentang Air Susu Ibu Eksklusif dengan Pemberian Air Susu Ibu Eksklusif di Wilayah Kerja Puskesmas Pembantu Hutatinggi Kecamatan Parmonangan Tahun 2019 - Ade Pryta Romanauli Simaremare (Universitas HKBP Nommensen, 2020)
Introduction : Exclusive breastfeeding means giving baby breast milk only since born until the age of 6 months. Based on data from the Provincial Health Office of North Sumatra in 2017, the achievement of exclusive breastfeeding at Aek Raja Public Health Center was only around 50%, considered to be very low. Factors that very influential on exclusive breastfeeding were limited knowledge, attitude, age, education and increased number of working mothers. Objective : To determine the relationship between level of knowledge, attitude, age, education level and mothers’ employment status regarding exclusive breastfeeding and provision of exclusive breastfeeding in the working area of ​​the Auxiliary Public Health Center of Hutatinggi Parmonangan Subdistrict in 2019. Method : This study was an analytical study with a cross-sectional design. Samples were selected consecutively and 67 respondents were obtained. Data were gained by questionnaires and analyzed using chi-square test. Results : The results of statistical tests obtained p value = 0,000 for the level of knowledge, attitude, age, education level and p value = 0,001 for employment status (p<0,05). This result means that there were relation between the level of knowledge, attitude, age, education level, and maternal employment status regarding exclusive breastfeeding and exclusive breastfeeding providing in the working area of ​​the Auxiliary Public Health Center of Hutatinggi Parmonangan Subdistrict in 2019. Conclusion : The exclusive breastfeeding was influenced by level of knowledge, attitude, age, education and employment status of mothers in the working area of ​​the Auxiliary Public Health Center of Hutatinggi Parmonangan Subdistrict in 2019. Keywords : Exclusive breastfeeding, knowledge and attitude, mother status.